Upaya Pencegahan Penularan TBC melalui Penyuluhan Rumah Sehat dan Pemasangan Cyclone Ventilator Modification (CVM) - Rusmiati Rusmiati; Ernita Sari; Putri Arida Ipmawati; Adnindya Krismahardi (Lembaga Pengembangan Kinerja Dosen, 2026)
Housing conditions in Kelurahan Taman Sidoarjo, are generally inadequate for health standards, characterized by natural ventilation of less than 15% of the floor area, limited lighting due to dense housing, poor air circulation, and high occupancy density. These conditions increase the risk of Tuberculosis (TB) transmission. This community service program aimed to improve public knowledge of healthy housing and clean and healthy living behavior,, as well as to enhance indoor air quality in TB patients’ houses through the application of the Cyclone Ventilator Modification (CVM). The activities included health education for 50 participants, family assistance for TB patients, and the installation of CVM in affected households. Evaluation results showed a significant improvement in participants’ knowledge, supported by a paired t-test (p < 0.001), indicating a meaningful difference between pre-test and post-test scores. Moreover, CVM installation contributed positively to improving indoor air quality. These findings suggest that combining education with the application of appropriate technology is effective in preventing TB transmission in densely populated areas. Therefore, CVM implementation should be expanded to other households and complemented with continuous health promotion to increase community awareness of healthy living environments.